GEOCAPABILITIES COMPETENCE OF HIGH SCHOOL GEOGRAPHY TEACHERS IN CENTRAL JAVA, INDONESIA; WHAT IS IT AND HOW DO WE ASSESS IT? - Dannis Ni'matussyahara; Sugiyanto Sugiyanto; Sarwono Sarwono (GeoEco, 2025)
GeoCapabilities aims to encourage the proposition of geography as a strong disciplinary knowledge and the role of teachers as the key in bringing knowledge to learners. This study aimed to determine the level of understanding of GeoCapabilities of geography teachers in high schools in Karanganyar Regency. The method used was descriptive qualitative, with 28 respondents. The type of research is qualitative with a descriptive approach. Data collection techniques include questionnaires, test questions, interviews, and documentation. Data analysis techniques using Interactive Model and Percentage. GeoCapabilities knowledge test results on each indicator obtained; 1. Geography imagination (26.16%), 2. Empathy (22.5%), 3. Integrative thinking (23.6%), 4. Spatial thinking (20.5%), 5. Exploration (29.25%). Based on the GeoCapabilities test results, the average score obtained by geography teachers is 3.6, with a maximum score achievement percentage of 46.6%. If the knowledge test score is in the range > 36% - 52%, it is included in the "low" category. The findings in this study imply that the low knowledge of GeoCapabilities of geography teachers can hinder the success of improving the quality of geography education. Therefore, to create continuity, it is necessary to measure the competence of geography teachers to evaluate the training needed in the future.